Microvascular Free Flap Reconstruction of Orbitocraniofacial Defects*. (April 2013) - Heffelfinger, Ryan; Murchison, Ann P.; Parkes, William; Krein, Howard; Curry, Joseph; Evans, James J.; Bilyk, Jurij R.
ABSTRACT Purpose: To examine the etiology, surgical extent and techniques, complications, and outcomes of microvascular free flaps (MFF) in the reconstruction of orbitocraniofacial defects. Design: A retrospective, institutional review board approved study was performed of all patients undergoing MFF to repair orbitocraniofacial defects over 51 months. Participants: Fifty-eight patients undergoing MFF to repair orbitocraniofacial defects were included. Material and Methods: Variables analyzed included demographics, etiology, resection area(s), donor site, flap size, duration of surgery, complications, length of hospital stay, flap survival, and mortality. Results: Fifty-eight patients underwent 61 MFFs from June 2007 to September 2011. The majority of patients were white (79.3%) and male (72.4%). The mean age was 64.1 years. The most common etiology was intraorbital and skull base extension of cutaneous squamous cell carcinoma (29.3%) followed by sinonasal squamous cell carcinoma (13.8%). Dura and/or brain were exposed in 44.8% of cases. MFFs were harvested from the anteriolateral thigh in 71.4% of cases with a 180.9 cm2 mean flap area. The mean length of hospital stay was 15.3 days and mean length of surgical time was 11 h and 17 min. Conclusions: Complex orbitocraniofacial defects require a multi-disciplinary team skilled in surgical extirpation and advanced reconstructive techniques. MFF should be considered in the management of large defects, especially when there is dura or brain exposure. Intensive postoperative monitoring is indicated for both systemic and flap-related complications. MMFs provide excellent coverage of large areas of exposed critical skull base structures, including dura and brain, and may allow for earlier adjuvant treatment.